FINANCIAL STATEMENTS AND IMPORTANT ASPECTS IN THEIR STRUCTURE: NATIONAL AND INTERNATIONAL EXPERIENCE - Abdibaeva, Tamara; Asadova, Shakhnoza (Science technology&Digital finance, 2024)
The article is afraid of the composition of financial statements and the goals of their compilation, classificatory aspects, national and international experiences of their compilation and presentation, comparative analysis.